Rare defect at superior helix as morphological variation of right auricle - Parwanto, Mauritius Lambertus Edy (International Journal of Research in Medical Sciences, 2018)
Auricle is the part of external ear. Morphological appearance and biometric of auricle are influenced by genetic and environmental factors. Base on the fact that morphological appearance and biometric of auricle vary in different human ethnic races. Normal of auricle have complete component with normal of dimension and appearance. Population studies show the different of morphological and biometric of auricle. Generally, the right and left auricles in the individual is symmetrical in both size and appearance. We reported about defect at superior helix of right auricle. In this case it shows that right and left auricles have complete components. The biometric comparison of right and left auricles showed equal or not significant different. Defect of right auricle at superior helix were indentation as morphological variation.